ER Stress and Autophagy - Lee, W.-S.; Yoo, W.-H.; Chae, H.-J. (Current Molecular Medicine, 2015)
Eukaryotic cells respond to various types of stresses caused by changes in the extracellular environment. Intracellular factors, such as the accumulation of misfolded proteins in the endoplasmic reticulum (ER), also cause stress and activate the unfolded protein response (UPR), which induces the expression of chaperones and proteins involved in the recovery process. However, if the stress is excessive or sustained, and ER function cannot be restored, the UPR triggers apoptosis, thereby removing the affected cell. It is now apparent that ER stress is also a potent trigger for autophagy, a self-degradative process that has an adaptive function. This review surveys the intersection of ER stress and autophagy and highlights the potential therapeutic implications thereof.
Keywords: chaperones